The ecological genetics of two populations of the house sparrow, Passer domesticus - Burke, Terence (1984)
The biochemical genetics of two natural populations of house sparrows, Passer domesticus, at sites 20km apart in Nottinghamshire, England, were investigated. Seven polymorphic protein loci were sampled non-destructively by taking blood samples from over 1500 individually marked birds. A detailed investigation of the genetics of these loci was conducted for 124 clutches containing 357 nestlings where the parents were also sampled. Segregations at four loci (6PGD, PEPD2, PEPD3 and lDHC) agreed with a simple Mendelian model of codominant inheritance. One locus (EST2) contained null alleles. Two loci (PEPD3 and GP1) showed segregation distortion in all sex, site and year classes. This distortion was not attributable to the misinterpretation of gel patterns; possible causes involving the operation of natural selection were discussed. Linkage analyses were conducted, and no significant evidence was obtained for linkage between any combination of loci.